Review Scopoletin – A Coumarin Phytoalexin with medicinal properties - Gnonlonfin, G.J.B.; Sanni, A.; Brimer, L. (Informa UK Limited, 2012)
Coumarins have been found in many plant species and some have antimicrobial and antifungal activities as well as pharmacological effects. Scopoletin (6-methoxy-7-hydroxycoumarin) is a coumarin compound with antifungal properties that has been isolated from several plant species. Although it is not yet fully understood, the biosynthesis of scopoletin is described. In addition, its induction upon attack by pathogens and abiotic stress as well as its inhibitory effects on bacteria and fungi are summarized in this review. The scientific information on the inhibitory effect of scopoletin on storage fungi is scarce.